A Gift of Nimrud Sculptures - Dyson Jr., Robert H.
1. Head of horn-mitred figure. Slab — 2. Horse-headed fig. Slab. — 3. Horn-mitred fig. in act of lustration — 4. Bird-headed fig. in act of lustration — 5. Detail. Hand with cone and sacred tree — 6. Detail. Hand holding ritual basket — 7. Lustration of sacred tree — 8. Ashurnasirpal and winged genius.